North Korean art : the enigmatic world of Chosonhwa - Muhn, BG, 1954- (Seoul Selection U.S.A., 2019)
"This book is dedicated to the people of the Korean Peninsula and seeks to shed light on an area of art history that has long been virtually unknown and unseen. It is a collection of visual information focusing on chosonhwa, the North Korean name for traditional ink wash painting on mulberry paper. At the same time, it is the product of a deep exploration within the history and culture of North Korean, South Korean, and Chinese art"--